Toxicity of imidacloprid gel bait against laboratory strain of Periplaneta americana (L.) (Dictyoptera : Blattidae) and Blattella germanica (L.)(Dictyoptera : Blattellidae) - Wan-Norafikah Othman,; Lee, H. L.; Sofian-Azirun M.,; Nura-Muna A. H.,; Chen, C. D. (Penerbit Universiti Kebangsaan Malaysia, 2017)
The efficacy of a 2.15% imidacloprid gel bait against laboratory strain Periplaneta americana and Blattella germanica was evaluated under laboratory conditions. The susceptibility trend of both species towards imidacloprid was: adult male < adult female < nymphs. All stages of both species were dead within 10 days in primary poisoning testing. Periplaneta americana adult male (LT50 = 0.47 h; LT95 = 5.24 h) died fastest, while nymphs of B. germanica took the longest time to reach 95% mortality (LT95 = 43.84 h). In indirect exposure via secondary poisoning, only adult males of P. americana (LT50 = 100.63 h) and B. germanica (LT50 = 54.66 h) obtained 50% mortality before the testing ended. No complete mortalities were achieved in any stages of both species within 10 days of secondary poisoning testing. Therefore, imidacloprid gel bait used in this study was able to cause complete mortalities within less than 2 days of 10-day primary poisoning testing but less effective in the 10-day secondary poisoning testing.